2020
DOI: 10.1172/jci133753
|View full text |Cite
|
Sign up to set email alerts
|

Salt-inducible kinase 1 maintains HDAC7 stability to promote pathologic cardiac remodeling

Abstract: BGB is a cofounder of, consultant to, and shareholder in Tenaya Therapeutics. SMH is an executive and officer of and shareholder in Amgen. SMH is a cofounder of and shareholder in Tenaya Therapeutics. NSG is a founder and science advisory board member of and equity holder in Gatekeeper, Syros, Petra, C4 Therapeutics, B2S Life Sciences, and Soltego. The Gray laboratory receives or has received research funding from Novartis,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(40 citation statements)
references
References 29 publications
1
39
0
Order By: Relevance
“…SIK1 acts as a key modulator in many physiological processes, including gluconeogenesis, cellular metabolism and growth (Hsu et al, 2020 ; Liu et al, 2020 ). Nixon et al suggested that SIK1 promotes insulin resistance on a high fat diet in skeletal muscle (Nixon et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…SIK1 acts as a key modulator in many physiological processes, including gluconeogenesis, cellular metabolism and growth (Hsu et al, 2020 ; Liu et al, 2020 ). Nixon et al suggested that SIK1 promotes insulin resistance on a high fat diet in skeletal muscle (Nixon et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…The mechanism by which the synaptic function of the SIK1-MT mice shifts to excitatory dominant remains unknown. SIK has been shown to regulate the subcellular localization and the biological activities of the class IIa histone deacetylases (HDAC4/5/7/9) (Berdeaux et al, 2007 ; Abend et al, 2017 ; Hsu et al, 2020 ) and CRTCs 1, 2, and 3 (Koo et al, 2005 ; Jagannath et al, 2013 ; Nixon et al, 2016 ) through the phosphorylation. SIK1-WT was distributed in the nucleus in a punctate pattern, whereas the SIK1-MT was diffused to the cytoplasm ( Figure 1B ).…”
Section: Discussionmentioning
confidence: 99%
“…Chondrocyte differentiation, 43 osteocyte mechanotransduction 44 Cardiac deficiency HDAC6 Neuronal differentiation 45 Viable, no visible pathology HDAC7 Cardiac remodelling, 46 neuroprotection, 47 endochondral ossification 48 Embryonic lethality due to dilatation and rupture of blood vessels HDAC9 Cardiac gene expression, 49 vascular calcification 50 Cardiac deficiency HDAC10 Immunoregulation 51 Viable Class 4 HDAC11 Immunoregulation, 52 muscle metabolism, 53 myoblast differentiation 54 Viable pharmacophore layout in these classes is comprised of the metalbinder moiety, the linker and the surface recognition domain 71 ; the surface recognition domain is further subdivided into a polar connecting unit and a hydrophobic cap. 72 This layout was originally proposed based on the X-ray crystallographic studies of an HDAC1 homologue HDLP with suberoylhydroxamic acid (SAHA) and TSA.…”
Section: Hdac5mentioning
confidence: 99%